PENGARUH OBJECTIVE OF ISLAMIC BANKING DAN CUSTOMER SATISFACTION CUSTOMER LOYALTY PERBANKAN SYARIAH DI INDONESIA - Hana Putri Salsabila Bhakti; Ayu Ekasari (EBID: Ekonomi Bisnis Digital, 2025)
The expansion of Islamic banks in Indonesia has been notably swift. Despite the substantial number of banks and branch offices, the assets held by Islamic banks remain very modest in relation to those of conventional banks. Islamic banking in Indonesia, being a nascent business, must compete with regular banking. This research aims to assess the impact of the objectives of Islamic banking and customer satisfaction on customer loyalty within the Islamic banking sector in Indonesia. This research employs a quantitative methodology. The data collection employs a purposive sampling approach via the distribution of questionnaires, targeting persons who have been clients of an Islamic Bank for a minimum of two years, resulting in a sample of 151 respondents. This research reveals that the objectives of Islamic banking and customer satisfaction significantly influence customer loyalty within Islamic banking in Indonesia.